Technology-Enhanced Art and Sustainable Discourse Practices - Zaeri, Parisa; Roozafzai, Zahra Sadat (Talenta Publisher, 2024)
This study explored the potential of technology-enhanced art in fostering sustainable discourse practices and social connection in the digital age. As technology advances, new opportunities emerge to integrate digital tools into creative practices, particularly in the realm of art. By examining the intersection of art, technology, and discourse analysis through a sustainability lens, this research aims to uncover innovative approaches to promoting effective communication, civic engagement, collaboration, intercultural understanding, empathy, and resilience incorporating co-design processes, shared decision-making, or collaborative art-making activities. The study provides an overview of technology-enhanced art practices including social media, virtual reality, interactive installations, and digital storytelling tools, and their impact on discourse practices within diverse socio-cultural contexts. It investigates the role of digital platforms and creative processes in facilitating social connection through discourse. The research focuses on a thematic approach to technology-enhanced art interventions that promote sustainable discourse practices and social connection. Through a thematic and intervention-based approach, this research combines a review of current literature with case studies showcasing the successful implementation of technology-enhanced art interventions. So the current study argues that technology-enhanced art holds significant potential for fostering sustainable discourse practices and social connection in the digital age. By harnessing the power of digital tools and creative processes in an environmentally conscious manner, artists, educators, and practitioners can support social connections. This, in turn, contributes to personal, social, and environmental resilience in a rapidly evolving technological landscape.